2019
DOI: 10.1002/bdr2.1597
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic paralysis: Evaluation in infants with congenital Zika syndrome

Abstract: Background: Paralysis of the diaphragm in newborn infants can lead to recurrent infections and life-threatening respiratory insufficiency. The clinical diagnosis of unilateral diaphragmatic paralysis has been reported in infants with laboratory evidence of congenital Zika virus infection and/or the congenital Zika syndrome (CZS) phenotype but no evaluation of phrenic nerve function has been described.All reported infants have had accompanying arthrogryposis. High infant mortality is reported. Methods: The caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…All the papers that evaluated the central nervous system found neurological alterations, and the main ones were seizure, epilepsy, irritability, pyramidal syndrome, sleep disorders, and hyperexcitability ( 5 , 12 , 18 , 19 , 27 , 31 , 35 , 36 , 42 , 45 , 46 , 48 , 50 , 51 , 54 , 56 , 61 , 62 , 66 , 69 71 , 74 , 77 ). Regarding neuro-psychomotor development, all 15 papers reported motor, cognitive, or language delay ( 10 , 11 , 15 , 17 , 18 , 24 , 32 , 33 , 44 , 47 , 52 , 58 , 61 , 62 , 65 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the papers that evaluated the central nervous system found neurological alterations, and the main ones were seizure, epilepsy, irritability, pyramidal syndrome, sleep disorders, and hyperexcitability ( 5 , 12 , 18 , 19 , 27 , 31 , 35 , 36 , 42 , 45 , 46 , 48 , 50 , 51 , 54 , 56 , 61 , 62 , 66 , 69 71 , 74 , 77 ). Regarding neuro-psychomotor development, all 15 papers reported motor, cognitive, or language delay ( 10 , 11 , 15 , 17 , 18 , 24 , 32 , 33 , 44 , 47 , 52 , 58 , 61 , 62 , 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding genitourinary characteristics, studies reported neurogenic bladder and cryptorchidism ( 22 , 23 , 72 ). The most common orthopedic alteration was arthrogryposis ( 12 , 16 , 21 , 36 , 42 , 46 , 57 ). All papers that evaluated gastrointestinal manifestations reported dysphagia ( 38 , 46 , 48 , 61 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brainstem cranial nerves are often affected, leading to oromotor dysfunction, persistent swallowing disorders and respiratory problems ( Pereira et al, 2020 ). Diaphragmatic paralysis due to the phrenic nerve dysfunction was reported in 3 of 120 (3.6%) infants with CZS with the need for assisted ventilation, and led to early death ( van der Linden et al, 2019a ).…”
Section: Congenital Zika Syndromementioning
confidence: 99%
“…van der Linden et al, 2016). Another defect more recently identified as associated with congenital Zika virus infection is diaphragmatic paralysis due to phrenic nerve palsy (Rajapakse et al, 2018;V. van der Linden et al, 2019).…”
Section: Zika Virus and Birth Defectsmentioning
confidence: 99%